Studi Eksperimental Pengelasan Baja Karbon Rendah Menggunakan Pengelasan Smaw Sistem Sliding Adaptive Two Axis Dengan Variasi Sudut Elektroda - Uberkis Uberkis; Yohanes Yohanes (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
SMAW welding (shield metal arc welding) has advantages in the current and welding angle that can be varied, and the penetration width of the electrode melting can be adjusted. This study uses a SMAW welding machine with a sliding adaptive two axis system design so that the electrode angle in the welding process is constant, this design is the development of a vertical sliding adaptive system. This study varied the angle of the electrode to find out the results welding from the SMAW welding machine with the sliding adaptive two axis system. In this study the characteristics of welds are based on visual observations and mechanical properties using a tensile test. The parameters varied were the electrode angles 45°, 70°, and 90°. the welding speed controlled by Arduino Uno. The material used was low carbon steel, using campuh V with a slope angle of 60°. In this study the metal splicing area that had the highest tensile strength was 533.44 MPa and the lowest value was 399.88 MPa with 9 specimens varied. The micro-welding structure is determined by many factors including heat input, current strength, welding speed, and cooling rate. In this study the HAZ region has a larger grain structure than the base metal and weld metal.Keywords: smaw welding, sliding adaptive two axis, electrode angle, seam v.